The highly divergent New World Artemia species (Branchiopoda, Anostraca), A. franciscana and A. persimilis, show subtle differences in morphological traits involved in mating - Mura, Graziella; Gajardo, Gonzalo (Zootaxa, 2011)
Mate choice significantly impacts upon population divergence and therefore speciation, recognition of equals being critical in cases where species and divergent populations coexist. The New World species of the brine shrimp Artemia, A. franciscana and A. persimilis, were compared through Scanning Electron Microscopy (SEM) for the following traits: shape and ornamentation of spine-like projections on the basal part of the penes; relative size, shape and ornamentation of the frontal knobs; cuticolar cones on the male second antenna, and ovisac (brood pouch) morphology. In particular, frontal knobs, described as playing a role in maintaining riding pairs attached (amplexus), and ovisac morphology, grouped all individuals into the corresponding species, but these differences seem too subtle to prevent inter-specific mating. In other words, mating between both species would be unspecific (not a key-lock type), an expected finding for allopatric species that would not have the chance to reinforce reproductive mechanisms in sympatry, as predicted by the allopatric mode. Additionally, both species inhabit selectively differential habitats that would prevent viability of migrants. At the population level, A. franciscana locations at the southern edge of the species distribution in the Americas (Chile) showed variation to the typical A. franciscana pattern, a somewhat expected finding for peripheral populations. The saltworks at Pichilemu (34° S, central Chile) appear to be a special environment where individuals from both species could eventually coexist, as inferred by the hybrid-like appearance of some individuals. This type of environment facilitates the testing of novel morphological variants which may affect the shaping of morphological divergence.